A new lunar high-Ti basalt type defined from clasts in Apollo 16 breccia 60639. (15th January 2016) - Fagan, A.L.; Neal, C.R.
Abstract: This paper reports the detailed examination of three basalt clasts from Apollo 16 breccia 60639 that represent a new variant of high-Ti basalt returned from the Moon by the Apollo 16 mission. Mineral chemistry and whole-rock analyses were conducted on aliquots from three clasts (breccia matrix, basalt, and basalt + breccia matrix). The basalt clasts, which are not overtly porphyritic, contain compositionally zoned pyroxene, olivine, and plagioclase crystals that represent the evolution of the magma during crystallization; ilmenite does not exhibit major-element compositional zoning within individual crystals. Mineral compositions are distinct between the basalt and breccia matrix lithologies. In addition, whole-rock analyses identify clear compositional differences between the basalt and breccia matrix lithologies in both major and trace element concentrations. The composition of the mixed lithology aliquots (i.e., basalt + breccia matrix) do not indicate simple two component mixing (i.e., compositions are not intermediate to the basalt and breccia end-members); this apparent incongruity can be accounted for by adding ∼19–40% plagioclase to an amalgamation of the average basalt and individual breccia clast compositions via impact mixing. Whole-rock analyses are consistent with previous analyses of one 60639 basalt clast, which were interpreted to indicate chemical similarity with Apollo 11 and 17 basalts. However, both major and trace elements suggest that the 60639 basalt clasts examined here have compositions that are distinct from Apollo 11 and 17 high-Ti basalts. Although the 60639 basalt clasts have similar characteristics to a variety of previously identified basalt types, the more extensive whole-rock analyses reported here indicate that they represent a type of Apollo high-Ti basalt heretofore unrecognized in the Apollo and lunar meteorite collections. By placing these new analyses in the context of other mare basalt compositions, a petrogenetic model for the basalts found in breccia 60639 is presented.